2003
DOI: 10.2116/analsci.19.859
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatographic Determination of Fluvoxamine and Fluvoxamino Acid in Human Plasma

Abstract: IntroductionFluvoxamine, 5-methyl-4′-trifluoromethylvalerophenone(E)-O-2-aminoethyloxime monomaleate, is one of several antidepressant agents known as selective serotonin reuptake inhibitors (SSRIS). The efficacy of fluvoxamine in depression has been reviewed in previous papers. 1,2 The clinical pharmacokinetics of fluvoxamine were also described in a previous paper. 3 Negligible amounts of fluvoxamine are excreted unchanged in the human urine. Urinary fluvoxamine metabolites have been identified as consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Most FVX analysis is performed by high-perfor-mance liquid chromatography (HPLC) coupled with spectrometric detectors, ultraviolet/diode array [4][5][6][7][8][9][10][11][12][13][14][15][16][17], mass spectrometric [18,19] and fluorimetric [20][21][22], for analysis of pharmaceuticals [8] and human serum or plasma [4][5][6][7][10][11][12][13][14][15][16][17][18][19][20][21][22]. This widespread usage of HPLC methods is justified by the high sensitivity and the low limit of detection usually obtained and the possibility of simultaneous analysis of the drug and its metabolites, which increases its use even further.…”
Section: Introductionmentioning
confidence: 99%
“…Most FVX analysis is performed by high-perfor-mance liquid chromatography (HPLC) coupled with spectrometric detectors, ultraviolet/diode array [4][5][6][7][8][9][10][11][12][13][14][15][16][17], mass spectrometric [18,19] and fluorimetric [20][21][22], for analysis of pharmaceuticals [8] and human serum or plasma [4][5][6][7][10][11][12][13][14][15][16][17][18][19][20][21][22]. This widespread usage of HPLC methods is justified by the high sensitivity and the low limit of detection usually obtained and the possibility of simultaneous analysis of the drug and its metabolites, which increases its use even further.…”
Section: Introductionmentioning
confidence: 99%
“…The present study analyzed the data from previous prospective pharmacogenetic [17,18,19,20] and pharmacokinetic [21,22] studies that had been reported individually. For the present study, subjects treated with fluvoxamine were added to those in our previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…The GR Bcl1 polymorphism was determined by PCR restriction fragment length polymorphism as previously reported [22]. Samples (20 μl) were of a PCR mixture containing 100 ng of genomic DNA template, 1.5 m M MgCl 2 , each 0.5 μmol of forward primer (5′-TGC TGC CTT ATT TGT AAA TTC GE-3′) and reverse primer (5′-AAG CTT AAC AAT TTT GGC CAT C-3′), 200 μ M of dNTP mixture and 1.25 units of HotStar Taq DNA polymerase (Qiagen, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual dose of FLV ranges from 50 to 300 mg per day, and the steady-state plasma concentration is correlated with the therapeutic outcome (Wilde et al, 1993;Kent et al, 2000). FLV is absorbed well following oral administration, with the plasma concentration peaking after 2-8 h; it is extensively bound to plasma proteins (77%) and has a wide intersubject variability in its elimination half-life (Katzung, 2001;Ohkubo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%